Respuesta :
h(x) = (x – 2)2 - 7
This is because you can find the vertex to be (2, -7) using the x value of the vertex as -b/2a and the y equal to the output of that. You can then plug them into the vertex form equation.
This is because you can find the vertex to be (2, -7) using the x value of the vertex as -b/2a and the y equal to the output of that. You can then plug them into the vertex form equation.
Answer: Vertex form [tex]y=(x-2)^2-7[/tex].
[tex]y=(x-2)^2-7[/tex] is the shifted 2 units right and 7 units down.
Step-by-step explanation: Given function f(x)=[tex]x^2-4x-3.[/tex]
We need to write it in vertex from.
In order to write it in vertex form, we need to find the values of a, b and c for the given quadratic function.
a=1, b=-4 and x=3.
x-coordinate of the vertex = -b/2a = - (-4)/2(1) = 4/2 = 2.
Plugging x=2 in given function to get the value of y-coordinate of the vertex.
[tex]f(2) = (2)^2-4(2)-3 = 4-8-3 =-7.[/tex]
Therefore, we got vertex (h,k) at (2,-7)
Plugging values of a, h and k in vertex form [tex]y=a(x-h)^2+k[/tex]
[tex]y=(x-2)^2-7[/tex].
Therefore, vertex form is [tex]y=(x-2)^2-7[/tex].
Given parent function [tex]f(x)=x^2.[/tex]
According to rules of transformations,
y=f(x-m) will translate m units right and
y= f(x) - n will translate n units down.